2006
DOI: 10.4102/sajp.v62i4.163
|View full text |Cite
|
Sign up to set email alerts
|

Health education needs among individuals with low back pain

Abstract: Lack of positive results from many of the health-education programmes for patients with low-back pain (LBP) is possibly due to the type of health information that may have been presented and the method that had been used. The present study sought to explore health-education needs among individuals with LBP. A qualitative approach that utilised in-depth interviews and a focus-group discussion was used. Data was drawn from ten participants attending physiotherapy treatment due to a non-specific LBP at the Nairob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Only 25% of participants selected tumors, infections, and fractures, while half of them chose cold and old age. Nyagah and Merle [ 28 ] found that most patients living with LBP lack knowledge about its causes and contributing factors. Other studies have revealed that the general population, including patients diagnosed with LBP, has poor knowledge and awareness about the causes and contributing factors of LBP [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 25% of participants selected tumors, infections, and fractures, while half of them chose cold and old age. Nyagah and Merle [ 28 ] found that most patients living with LBP lack knowledge about its causes and contributing factors. Other studies have revealed that the general population, including patients diagnosed with LBP, has poor knowledge and awareness about the causes and contributing factors of LBP [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%